Neoplasms of the cecal appendix: analysis of a multicenter casuistry About seven cases - Ribero, Gustavo; Acevedo, Carlos; Cimarra, Fernando; Genta, Fernando (Cirugía del Uruguay, 1998)
The authors present the analysis of a multicentric samp/e of neoplasia of the cecal appendix, and make a bibliographica/ review of this subject. They describe casuistry emphasizing treatment of malignant lesions and indications far secondary right hemicolectomy.